2024
DOI: 10.3345/cep.2023.00794
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 among infants: key clinical features and remaining controversies

Nevio Cimolai

Abstract: Infants aged <1 year represent a seemingly more susceptible pediatric subset for infections. Despite this, coronavirus disease 2019 (COVID-19) infection has not been proven as more serious in this age group (outside the very early neonatal period) than in others. Indeed, a considerable number of asymptomatic infections have been recorded, and the symptoms and morbidity associated with COVID- 19 differ minimally from those of other respiratory viral infections. Whether due to an abundance of caution or truly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 174 publications
0
3
0
Order By: Relevance
“…Studies have reported that among infants, although COVID-19 is symptomatically mild, even the low risk of severe infection would require prevention. The presence of comorbid conditions can heighten the risk of infections and their complications in infants [33]. Therefore, it is imperative to focus on protecting the infants from COVID-19 infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that among infants, although COVID-19 is symptomatically mild, even the low risk of severe infection would require prevention. The presence of comorbid conditions can heighten the risk of infections and their complications in infants [33]. Therefore, it is imperative to focus on protecting the infants from COVID-19 infections.…”
Section: Discussionmentioning
confidence: 99%
“…As infants under 6 months of age are ineligible for any existing COVID-19 vaccines, maternal vaccination is the only available option in preventing disease in early infancy. It is noted that infants acquire immunity via the placenta from their mothers [33,34]. A recent study conducted in the US reported that the incidence of hospitalization for COVID-19 was considerably lower for infants aged < 6 months if their mothers were vaccinated compared with infants of unvaccinated mothers (21/100,000 person-years vs. 100/100,000 person-years) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Purposeful screening of asymptomatic patients or having a large fraction of such patients out of the total so tested adds another layer of diagnostic bias. Asymptomatic infection has been known to be commonplace in presumed paediatric SARS‐CoV‐2 infections, but the veritable frequency of the same can be challenged 3 . As for the potential bias in the current study, the influence of variable laboratory diagnostics can also affect other viral amplification diagnostics.…”
mentioning
confidence: 92%